Dengue and risk factors for severe forms - Ayang de Morais, Darlan; Carnovale, Susana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Dengue is a disease of viral etiology transmitted through the bite of infected mosquitoes, mainly by Aedes aegypti. It is an RNA virus that belongs to the Flavivirus family of which four serotypes are recognized: DENV 1, DENV 2, DENV3 and DENV 4 that present different antigenic properties. The difference between these serotypes lies in the amino acid sequence in the structural envelope protein. The prevalence of dengue virus infection varies depending on the region, environmental temperature, population development and economic conditions of the affected region, among other factors. The severity of dengue cases varies from mild symptoms such as headache, fever, general malaise, adynamia and retro-orbital pain, which characterize classic dengue (CD) as a self-limited infection, to severe cases that present the same general symptoms, but accompanied by bleeding and hemodynamic instability from the fourth day of infection that characterize dengue hemorrhagic fever (DHF or DSS) Dengue virus infection is prevalent in tropical and subtropical countries. According to the World Health Organization (WHO), it is estimated that there are approximately 100 million cases of CD and about half a million cases of DHF annually in the world. Primary infection with a DENV serotype induces serotype-specific or homotypic immunity and little heterotypic immunity. However, in secondary infections due to a different serotype compared to the primary infection, it could cause exacerbated reactions of the immune system, causing severe forms in the host (DHF or DSS). Objectives: To evaluate the risk factors for the presentation of severe forms of dengue and prognostic biomarkers in the case of DH. Material and methods: A systematic review of the publications located on the Pub Med platform, Google academic and SciELO of the last 10 years, on the topic of study. Conclusion: The severity of dengue depends on multiple factors, including the presence of comorbidities, alterations in clinical and laboratory markers, as well as the host’s immune response. Early identification of warning signs and appropriate clinical management of patients with dengue are essential to reduce the morbidity and mortality associated with the disease. Furthermore, new research is necessary to detect new specific biomarkers predictive of severe forms of dengue that allow correct management of these at-risk patients